Representing Iranian-Islamic Identity in Iranian Contemporary Cities Structure - MARYAM KAMYAR; ZAHRA JAFARI SPOUREZI (Alanya Hamdullah Emin Paşa Üniversitesi, 2019)
Urban identity could be considered as the result of interaction between social identity system and urbanism system. The term “Islamic City” is defined only by considering the physics of the city and reducing the concept of the city to physical elements. Current researches are carried out without considering the relationships between elements and parts of the Islamic city. The main objective in this research is to focus on the principles governing Islamic city which have their roots in Iranian identity and govern aspects of urban life, such as social, political, economic and physical space of the city. Studying concepts of centre, periphery and communications as the main elements of urban identity and matching each of the physical elements in aforementioned arenas could help with understanding the Islamic city structure and its organization and relations governing it. The significance of religious, social, and economic elements in the Islamic city matches the Contemporary urbanism identity in Iran and the concept of centre-periphery theory.